Reclaiming Spaces from the Margins - Faza Siddiq (PCD Journal, 2026)
This article explores the social production of participatory spaces, its effect on the participatory mechanisms, and how marginalised groups could reshape these spaces to claim their rights. The issue of housing the poor in Indonesia has rarely been a participatory process and is dominated by state-led evictions and government-controlled public housing. A recent initiative proposed by urban poor social movements, termed kampung susun attempted to shift decision-making and empower the marginalised. Despite early successful attempts, not all have managed to deliver changes smoothly. This article aims to investigate how these spaces of participation could fail to achieve transformative results and what kinds of opportunities exist for reclaiming decisive participation. The study argues that existing power relations and prevailing political culture of the local bureaucracy, state-owned company, and even within the urban poor hinders attempts at delivering the desired outcome for the movement. Nevertheless, avenues of reshaping spaces still exist through electoral institutions and the act of creating their own spaces of engagement.